Child observation a guide for students of early childhood - Palaiologou, Ioanna (SAGE/Learning Matters, 2016)
This is a key text for all those studying for degrees and foundation degrees in early childhood, early years and related disciplines and for Early Years Teacher candidates. It enables students to appreciate and understand the central role of observation for understanding, planning for and educating early years children. -- Provided by publisher.